Strategi RSUD Tenriawaru Kabupaten Bone Menuju Implementasi Sistem Pembayaran Prospektif - Bausat, Nurhidayat (UI Scholars Hub, 2015)
The main source of hospital income came from inpatients delivery care of Jamkesda. Jamkesda integration into BPJS health will change it’s payment system to provider from retrospective to prospective. This study aims to describe the potential difference of hospital tariff based on Perda and INA-CBGs. In addition hospital strategies to coping with potential difference of hospital is also observed. This study is an operational research collecting quantitative and qualitative data, using 660 claims and medical records of inpatient delivery care of Jamkesda year 2013. The results showed that the largest claim components for spontaneous delivery and delivery with (forceps, vacuum extraction, induction) are facilities/accommodation, medical and nursing fee. While the largest claim components for delivery with secarian are medical fee, consumables and facilities/accommodation. Spontaneous delivery showed a positive difference for all cases, while delivery with (forceps, vacuum extraction, induction) showed overall positive difference, but the difference between all cases varied. The largest difference found in secarian delivery with secarian is in the average of Rp.3.373.669/patient. It takes strategy through medical staff, nurses and pharmacy staff management with performance-based remuneration system, monitoring by clinical pathways to reduce length of stay and control of cost variations in delivery care, hospital formulary and standard of consumables, the use of hospital management information system for evaluation of hospital efficiency and addition of coders, costing for tariff, services and market identification to obtain subsidize potention and development of hospital services.